Republic of Tunisia : Information and Communications Technology Contribution to Growth and Employment Generation, Volume 1. Policy Note - World Bank (Washington, DC, 2014)
This policy note is the first of two volumes, drafted in conjunction with a more detailed technical report. It was prepared in response to a request by the Government of Tunisia for Bank assistance to formulate an ICT development strategy, in accordance with the targets set in the Government of Tunisia's 10th development plan. The policy note highlights current constraints to ICT sector development and proposes measures to eliminate them. It should be read in conjunction with the broader strategy report (volume two: technical report), which contains complementary data and technical information. The Government objectives were conveyed to the World Bank team in May 2001. The strategy is aimed at bolstering the country's emerging ICT sector and maximizing its ability to compete in local, regional, and global markets. In this context, the major objectives of the ICT strategy are to: (a) maximize the ICT contribution to growth and employment generation; (b) position Tunisia in the global ICT market; and (c) integrate ICT into the Tunisian economy. Indirect issues of the ICT impact on productivity and competitiveness are marginally treated in this note. The report compares the state of ICT development in Tunisia that of other economies, taking into account Tunisia's relative strengths and weaknesses in developing a competitive and robust ICT industry. The report outlines the pillars of a strategy and specifies measures to be implemented by the Government, the private sector, and other stakeholders.